Komparasi Mekanisme Penyelesaian Sengketa Pemilu di Beberapa Negara Penganut Paham Demokrasi Konstitusional - Bisariyadi Bisariyadi; Anna Triningsih; Meyrinda Rahmawaty H; Alia Harumdani W (Jurnal Konstitusi, 2016)
Every country in the world, moreover in every country which has implemented the way of life of democcratic and nation, presume that election is one of the important element as a marker of democracy of the country and also has a practical function of government political as a succession’s tool between the government parties and the oposition parties. In every democratic constitutional state, the election process has  a purpose to embody will of the people into pattern of power without violence.